Association of HLA-B27 Gene and Rheumatoid Arthritis: Analysis of Potential Role as a Predictive Biomarker - Khidhir, Karzan Ghafur; Ahmad, Baban; Sabir, Dana Khdr (Kurdistan Journal of Applied Research, 2024)
Rheumatoid arthritis (RA) is a predominant inflammatory arthritis in human. The function of HLA-B27 gene in other types of arthritis has been studied, however, its function in RA is unclear. This study investigated the relative expression of HLA-B27 gene in RA patients compared to normal control and assesses its suitability as a biomarker for early detection of RA. Bioinformatics analysis was used to determine the profile of HLA-B27 gene in different human tumors to demonstrate the possible involvement of HLA-B27 in both RA and cancer; and also, to discover its functional association with other human genes. Samples of human blood from RA patients and healthy individuals were collected, and RNA extraction, cDNA synthesis and qPCR were carried out to detect relative expression of HLA-B27. ROC analysis was undertaken to investigate HLA-B27 diagnostic performance; GENT2 platform was used to compare HLA-B27 expression levels in different human tumors, and gene-gene interaction network was generated using GeneMANIA to identify correlation of HLA-B27 with other human genes. The qPCR analysis demonstrated an increase in the HLA-B27 expression by 1.65 fold in RA compared to normal control. ROC analysis indicated that HLA-B27 expression could efficiently differentiate RA from normal, supporting its potential use as diagnostic molecular biomarkers. The GENT2 revealed that HLA-B27 expression levels vary across different tumor types, most notably in heart tissue. The gene-gene interaction network revealed that KIR3DL1, KIR3DS1, LILRB1, B2M and LILRA1 were the leading genes showing the highest correlations with the HLA-B27. Our results indicate that HLA-B27 gene is involved in the RA pathogenesis and it can be used as a molecular biomarker for the diagnosis of RA. Our findings could lead to the discovery of novel diagnostic, preventive and therapeutic strategies.